Practical application of cellular bioenergetics to the care of aged skin. (21st June 2013) - Osborne, R.; Carver, R.S.; Mullins, L.A.; Finlay, D.R.
Summary: In human skin fibroblasts in vitro, procollagen‐1 and NAD + /NADH were reduced in three strains of adult fibroblasts compared with neonatal fibroblasts. The levels of both procollagen‐1 and NAD + /NADH were increased in the adult fibroblasts by treatment for 24 (NAD energy) or 48 h (procollagen‐1) with a complex containing niacinamide, Pal‐KTTKS peptide and an olive oil fatty acid derivative (Olivem ® ), especially in combination with a natural extract from dill (Lys'lastine V ® ). In one of the adult fibroblast strains evaluated, these changes in procollagen‐1 and NAD + /NADH in response to the complex of bioactives were in parallel with increased expression of mRNA biomarkers related primarily to dermal matrix and basement membrane structure, including COL1A1, COL3A1, COL5A1, COL14A1, ELN and LOXL2, in addition to SOD2, NAMPT and TGFBR3 ; MMP1 was decreased in expression. In general, these mRNA biomarker effects were maintained or boosted by the addition of Lys'lastine V, particularly at 1%, and were similar to the fold changes in mRNA expression in neonatal compared with adult fibroblasts. These results indicate that the complex of niacinamide, Pal‐KTTKS and Olivem, especially with addition of Lys'lastine V, increases the NAD + /NADH bioenergy level of adult skin fibroblasts in parallel with increased expression of skin structure biomarkers in vitro to levels similar to those in younger fibroblasts. Thus, niacinamide, Pal‐KTTKS, Olivem and Lys'lastine V are promising bioactive candidates for inclusion in cosmetic formulations.